Exploring the Production of Secondary Metabolites from a Halophyte Tetragonia tetragonoides through Callus Culture - Ka Youn Lee; Do-Hyeon Nam; Yongsam Jeon; Sang Un Park; Jongki Cho; Md Ashrafuzzaman Gulandaz; Sun-Ok Chung; Geung-Joo Lee (Horticulturae, 2024)
Considering Korea’s gradual shift toward an aging society, consumer interest in compounds with physiological benefits, including antioxidant and anticancer effects, has surged. This study explored the potential of Tetragonia tetragonoides (Pall.) Kunze, commonly known as New Zealand Spinach (NZS), a halophyte with reported health benefits, including efficacy in treating gastrointestinal diseases, high blood pressure, diabetes, and obesity. This study also introduced a novel callus culture system for NZS, allowing for the rapid in vitro production of secondary metabolites. Optimal callus induction (100%) and biomass production (0.416 g) were achieved by adding 2.0 mg·L−1 6-BA (6-Benzylaminopurine) and 0.5 mg·L−1 2,4-D (2,4-Dichlorophenoxyacetic acid) among five auxin and cytokinin combinations. Two distinct callus types, TGC [TDZ (Thidiazuron)-supplemented Green Callus] and TNYC [TDZ + NAA (Naphthalene acetic acid)-supplemented Yellow Callus], were identified, each with unique characteristics. The calli showed total phenolic and flavonoid contents comparable to those of NZS leaves grown in the greenhouse. An expression analysis of six genes (CHS, CHI, F3H, F3′H, FLS, and DFR) involved in the kaempferol biosynthesis revealed an enhanced flavonoid biosynthesis-related gene expression in TGC, emphasizing its potential for compound production. GC-MS analysis identified distinct compound profiles in TGC and TNYC, with 2,3-butanediol and succinic acid being the predominant compounds among the nine and forty-four components, respectively. These calli offer a stable supply of functional compounds and present an environmentally sustainable solution. The derived callus culture system is anticipated to contribute to the development of healthy functional foods or pharmaceuticals from halophyte NZS.